A STUDY ON BIG DATA RETAIL BUSINESS ANALYTICS AND ITS IMPACT ON CUSTOMER RETENTION IN INDIAN RETAIL SECTOR (International Journal of Food and Nutritional Sciences, 2023)
The creation of so-called big data analytics has been sparked by the rapid expansion of the internet and the consumer-generated content it produces in order to better understand and address business issues as well as to seize opportunities. The recent increase of digital data has ushered a new era in business where decision-making is increasingly evidence-based. Large amounts of data is being collected, stored, and analysed by retail organisations, and various tools of big data analytics are used to carry on these processes. Retailers are aggressively looking for projects to use big data analytics to provide their consumers better services that provide mutual, previously unattainable benefits, which is not surprising given the massive volume of data generated by customers' transactions in retail outlets. Little empirical study has been done to explore and examine the aspects of big data analytics in the Indian retailing sector, despite the growing potential of big data. The purpose of this study is to ascertain how big data affects client retention in the Indian retail sector.